Recent advances of substitutionally doped tin dichalcogenides. Issue 20 (17th May 2022) - Zhang, Hao; Zhang, Zhenxiao; Zhan, Qing; Liu, Dongdong; Zhao, Puqin; Cheng, Yingchun
Abstract : Substitutionally doped tin dichalcogenides have potential for electric, photoelectric and thermoelectric applications. Abstract : Layered two-dimensional (2D) tin dichalcogenides (SnS2 and SnSe2 ) have attracted considerable attention owing to their environmental friendliness, semiconducting character, and outstanding electrical and optoelectronic properties. The electronic properties of 2D tin dichalcogenides can be effectively tuned by substitutional doping to improve their performance and extend their applications. Here, we review the recent advances in metal and non-metal substitutional doping of tin dichalcogenides and the effect of doping on electrical, optoelectronic, and thermoelectric applications. Moreover, the challenges and outlook of substitutional doping of tin dichalcogenides are also discussed.